(untitled) (LACCEI, 2024)
This article is the result of the diagnosis of the study of organizational culture in the engineering sector during the COVID-19 pandemic from 2019 to 2021. Likewise, studies on organizational culture are increasingly important in the current scenario, due to the influence as an intangible asset in the engineering sector, which is why this article aims to know the organizational culture and the relationship it has on the quality of service of a Peruvian company of Natural Gas, which contributes to the proper functioning and permanence of efficient work in organizations over time. The methodology used was quantitative approach, basic type, non-experimental design, causal correlational level and transactional scope, the sample was of 245 collaborators, two questionnaires were used, one for organizational culture with 15 items and the other for service quality with 16 items. The results were as follows: 21.2% (52) of the organizational culture variable was at a regular level 11.8% (29) stated that the quality of service was at a regular level and 9.4% (23) expressed that the quality of service was at a good level. Of the 78.8% (193) of the good level of the organizational culture variable, 11.8% (29) state that the quality of service has a fair level and 66.9% (164) state that the quality of service has a good level. It is concluded that the variability of the quality of service depends on 19.8% of the organizational culture in a natural gas company in Lima, Peru during the COVID-19 pandemic, therefore, at such a level of significance to achieve a good organizational culture should be put enough emphasis on the collaborators of the Peruvian company in order to enhance leadership, work approach and values, to achieve an effective and efficient quality of service to customers.